Relationship between ABO Blood Group with Severity, Length of Hospitalization, and Mortality Rate of COVID-19 Patients - Hanif Benazir Salsabillah Gani; Samad R; Julyani S; Rachmawati Muhiddin (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Previous research suggests that the ABO blood group may play a role in the immunopathogenesis of SARS-CoV-2 virus infection. The purpose of this study was to analyze the relationship between the ABO blood group and the severity, length of hospitalization, and mortality rate of COVID-19. A descriptive-analytic study with a cohort retrospective design, involving 257 research samples, was conducted. The statistical tests used in this research were the Kolmogorov-Smirnov test, the Chi-Square test, the Fisher Exact test, and the Kruskal-Wallis test. The test results were significant if the p-value <0.05. From the results of the study, it was found that the analysis of blood type with severity was not statistically significant (p> 0.05), as well as blood type with severity and length of treatment, there was no relationship between severity and length of stay in all blood groups (all with p>0.05) while for blood groups with severity and mortality, there was a relationship between blood type and high mortality in all blood groups (all with p<0.001). There was no relationship between blood type and severity of SARS-CoV-2 virus infection (all p>0.05). However, there was a significant relationship between criticality and high mortality in all blood groups (all with p<0.001). Pathophysiological mechanisms that explain the relationship between ABO blood type and SARS-CoV-2 infection, one of which is the presence of anti-A antibodies in group O individuals that bind to the A antigen in the viral envelope and block infection, in which blood group O has susceptibility to SARS virus infection. There is no relationship between ABO blood type and patient severity and length of stay, but there is a correlation between mortality and ABO blood type in COVID-19 patients.